WAWASAN PERUNDUNGAN DAN KAITANNYA DENGAN LOCAL WISDOM: STUDI TAFSIR AL-MISBAH, MARAH LABID, DAN TAFSIR AL-IBRIS - Ahmad Fawaid; Fadoilur Rohman (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2026)
Bullying remains a prevalent social issue, especially among adolescents, and requires analysis from the perspective of Qur’anic exegesis. This study aims to analyze Qur’anic verses related to bullying through the perspectives of Tafsir Al-Misbah, Marah Labid, and Tafsir Al-Ibris, as well as to examine their relationship with local wisdom values as a preventive effort in contemporary society. This research employs a library research method with a qualitative descriptive approach and thematic interpretation (maudhu’i). The findings indicate that bullying in the Qur’an includes behaviors such as mocking, insulting, and degrading others. Tafsir Al-Misbah emphasizes social ethics, Marah Labid highlights spiritual purification, while Tafsir Al-Ibris relates it to local cultural values such as politeness (unggah-ungguh). These values align with local wisdom such as empathy, cooperation, and respect, which can serve as a foundation for preventing bullying in society.